MOTIVATIONAL FACTORS IN ENGLISH LANGUAGE LEARNING: A STUDY OF FIRST-YEAR LAW STUDENTS AT TASHKENT STATE UNIVERSITY OF LAW - Umirov, Sarvar (PT. Antis International Publisher, 2025)
Objective: This study investigates the factors influencing motivation among English language learners (ELLs) at Tashkent State University of Law, focusing on first-year students enrolled in the